Terapi Kompresi pada Pasien Vena Varises yang Menjalani Operasi - Elin Hidayat; Abu Bakar; Retno Indarwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of compression therapy in varicose veins patients to reduce pain and increase wound healing after surgery. The method used was a systematic review using a checklist of protocols and rules (PRISMA) and a flowchart with the feasibility of studies assessed using the PICOT framework, searches using five databases, Science Direct, CINAHL, Scopus, SAGE, and ProQuest. The results showed that as many as ten articles were obtained discussing the effects of compression therapy in patients with varicose veins, with different discussions in each study bringing positive impacts. In conclusion, compression therapy is considered the most effective conservative treatment for varicose veins, which has been shown to benefit from several research results. Namely, compression improves the healing of varicose veins compared to no reduction. Still, compression therapy has not been proven to provide long-term effects—benefits for postoperative varicose veins patients to return to normal activities. Keywords: Surgery, Compression Therapy, Varicose Veins